Effects of Entrepreneurship Learning and Subjective Norms on Biology Students' Entrepreneurial Attitudes and Interests - M. Khairul Wazni; Agus Muliadi; Marhamah Marhamah; Sarwati Sarwati (Jurnal Penelitian Pendidikan IPA, 2023)
This study aims to determine the effect of entrepreneurship learning and subjective norms on students' entrepreneurial attitudes and interests. This study is a descriptive exploratory study with 33 biology education students as subjects. The research instrument used was a closed questionnaire with degraded answers according to the Likert scale and had been validated by experts. Analysis of research data used is descriptive statistics and inferential statistics with multiple linear regression test at a significance level of 5%. The results of the study show that (1) biology students' perceptions of entrepreneurship learning, subjective norms, attitudes and entrepreneurial interests are in the Good category; (2) there is an effect of entrepreneurship learning and subjective norms on student entrepreneurial attitudes with a significance value of 0.000 <0.05; (3) there is an effect of entrepreneurship learning and subjective norms on student entrepreneurial interest with a significance value of 0.000 <0.05; (4) entrepreneurship learning and subjective norms influence student entrepreneurial attitudes by 50.1% and the rest are influenced by variables or other factors; (5) entrepreneurship learning and subjective norms affect student entrepreneurial interest by 42.7% and the rest is influenced by variables or other factors.